Grassroots Business Intelligence as an Enabler of Change Management: A Case Study at a Large Global Manufacturing Firm - Makoto Nakayama; Öykü Isik; Norma Sutcliffe; Sebastian Olbrich (Complex Systems Informatics and Modeling Quarterly)
Business intelligence (BI) has attracted considerable attention in recent years. Despite the hype, BI frequently suffers from broad definitions, unrealistic expectations, and the incongruities of IT needs between headquarters and local business units. We report the findings of a case study at a large international manufacturing firm headquartered in the EU. The firm wants to transform itself from a conservative firm with traditional values to a more entrepreneurial and nimble organization with its supply chains driven by Industry 4.0 and the Internet of Things (IoT). The firm is going through its transformation, focusing on the BI system. Our observations suggest that firms consider BI to be the enabler of change management rather than simply technical tools that extend the traditional systems environment.